Compliance of Hospitals in Saudi Arabia with National and International Medical Gas Pipeline System Maintenance Guidelines - Altinawi, Amir; Javed, Ravish; Abdulwahed, Abdullah Salem; Alqahtani, Mahdi (British Journal of Healthcare and Medical Research, 2024)
The aim of this study has two folds. Firstly, to investigate the extent to which hospitals in Saudi Arabia adhere to CBAHI (Saudi Central Board for Accreditation of Healthcare Institutions) standards regarding maintenance of medical gas pipeline systems (MGPS). Secondly, to determine if different hospitals implement the MGPS check-points required by CBAHI in a similar manner with respect to timeframe of performing the check-points. A cross-sectional survey was conducted during field visits to 11 hospitals biomedical engineering offices. A paper-based questionnaire was developed to collect all the relevant information. The study results showed that 99% of the check-points specified by CBAHI are implemented fully by all the 11 hospitals. There was only one hospital that failed-short of checking the system alarm of the pipeline system, and another hospital that failed-short of checking for leak-signs in joints of liquid oxygen plant. There were large variations in time-periods of actually performing the required check-points among hospitals. The study suggests modification on CBAHI standards regarding maintenance and operation of MGPS that incorporate timeframe for performing each check-point to guarantee an efficient and safe MGPS.